2013
DOI: 10.1038/nature11984
|View full text |Cite
|
Sign up to set email alerts
|

Induction of pathogenic TH17 cells by inducible salt-sensing kinase SGK1

Abstract: Th17 cells are highly proinflammatory cells critical for clearing extracellular pathogens and for induction of multiple autoimmune diseases1. IL-23 plays a critical role in stabilizing and reinforcing the Th17 phenotype by increasing expression of IL-23 receptor (IL-23R) and endowing Th17 cells with pathogenic effector functions2, 3. However, the precise molecular mechanism by which IL-23 sustains the Th17 response and induces pathogenic effector functions has not been elucidated. Here, we used transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

52
973
10
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 898 publications
(1,076 citation statements)
references
References 23 publications
52
973
10
7
Order By: Relevance
“…In agreement with these findings, T H 17 cells generated under salt‐enriched conditions show a highly pathogenic phenotype in vitro 74, 75. This increase in T H 17 responses under high salt conditions was shown to be mediated by p38 mitogen‐activated protein kinase (MAPK), nuclear factor of activated T cells (NFAT5), and serum glucocorticoid kinase‐1 (SGK1) 74, 75. Consistently, a T cell–specific knockout of Sgk1 in mice ameliorated EAE disease severity that was seen on a high salt diet 75.…”
Section: Salt and Mssupporting
confidence: 83%
See 2 more Smart Citations
“…In agreement with these findings, T H 17 cells generated under salt‐enriched conditions show a highly pathogenic phenotype in vitro 74, 75. This increase in T H 17 responses under high salt conditions was shown to be mediated by p38 mitogen‐activated protein kinase (MAPK), nuclear factor of activated T cells (NFAT5), and serum glucocorticoid kinase‐1 (SGK1) 74, 75. Consistently, a T cell–specific knockout of Sgk1 in mice ameliorated EAE disease severity that was seen on a high salt diet 75.…”
Section: Salt and Mssupporting
confidence: 83%
“…A possible explanation of these divergent results is the different treatments and baseline characteristics of the MS patients included in the studies, as well as the divergent approaches to assess sodium intake in these retrospective analyses. Several studies have shown that high sodium diets could exacerbate EAE 74, 75, 77, 79. When analyzing CD4 + T cells, this effect was accompanied by increased numbers of T H 17 cells and a higher infiltration of T H 17 cells into the CNS 74, 75.…”
Section: Salt and Msmentioning
confidence: 99%
See 1 more Smart Citation
“…High salt intake also induces the intrarenal aldosterone receptor and promotes renal fibrotic injury (15). Two recent studies identified that increased dietary salt intake promotes tissue inflammation by triggering IL-17-producing CD4 + T cell development (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…This condition is known as autoimmunity. Hence high intake of sodium produces high immune cells like helper T cells which attack healthy tissues by producing protein interleukin [27][28] .…”
Section: Effect Of Saltmentioning
confidence: 99%